2006
DOI: 10.1093/pcp/pcj090
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Affects Cortical Microtubule Organization and Helical Growth in Arabidopsis

Abstract: Cortical microtubule arrays are critical in determining the growth axis of diffusely growing plant cells, and various environmental and physiological factors are known to affect the array organization. Microtubule organization is partly disrupted in the spiral1 mutant of Arabidopsis thaliana, which displays a right-handed helical growth phenotype in rapidly elongating epidermal cells. We show here that mutations in the plasma membrane Na(+)/H(+) antiporter SOS1 and its regulatory kinase SOS2 efficiently suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 44 publications
4
89
0
Order By: Relevance
“…The idea that +TIPs, and SPR1 in particular, may be targets of environmental signaling is supported further by studies of salt stress. Wang et al (2011) found that salt stress led to the 26S proteasome-based degradation of SPR1 protein, while Shoji et al (2006) found that salt stress affected cortical MT array organization and suppressed the right-handed helical growth phenotype of spr1 mutant roots.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that +TIPs, and SPR1 in particular, may be targets of environmental signaling is supported further by studies of salt stress. Wang et al (2011) found that salt stress led to the 26S proteasome-based degradation of SPR1 protein, while Shoji et al (2006) found that salt stress affected cortical MT array organization and suppressed the right-handed helical growth phenotype of spr1 mutant roots.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule reorganization and/or apparent depolymerization occurs in response to specific abiotic stimuli (Bartolo and Carter, 1991;Himmelspach et al, 1999;Shoji et al, 2006). Several examples of the microtubule cytoskeleton alterations in response to biotic stimuli, such as infection by pathogenic fungi or symbiotic interactions with mycorrhiza or rhizobia, exist (for review, see Takemoto and Hardham, 2004).…”
Section: Signal-mediated Cortical Microtubule Reorganization/depolymementioning
confidence: 99%
“…Cortical microtubules are also involved in signal-response coupling. It has been shown that abiotic stimuli, such as gravity (Himmelspach et al, 1999), hormones (Shibaoka, 1994), freezing (Bartolo and Carter, 1991), and salt stress (Shoji et al, 2006), result in the reorientation or depolymerization of microtubules. Biotic interactions resulting in microtubule alterations also exist.…”
mentioning
confidence: 99%
“…[13][14][15] It has been well documented MTs and MFs take part in salt stress, heat shock, dehydration and drought. 10,12,13,[15][16][17][18] However, the exact mechanisms about how MTs and MFs sense cues and reorganize themselves in these processes remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%